2015
DOI: 10.1186/s12929-015-0144-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroregenerative effects of olfactory ensheathing cells transplanted in a multi-layered conductive nanofibrous conduit in peripheral nerve repair in rats

Abstract: BackgroundThe purpose of this study was to evaluate the efficacy of a multi-layered conductive nanofibrous hollow conduit in combination with olfactory ensheathing cells (OEC) to promote peripheral nerve regeneration. We aimed to harness both the topographical and electrical cues of the aligned conductive nanofibrous single-walled carbon nanotube/ poly (L-lactic acid) (SWCNT/PLLA) scaffolds along with the neurotrophic features of OEC in a nerve tissue engineered approach.ResultsWe demonstrated that SWCNT/PLLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 45 publications
2
23
0
1
Order By: Relevance
“…For example, Ahn et al reported the in vivo functions of CNT‐interfaced nerve conduits in the regeneration of transected rat sciatic nerve . Kabiri et al evaluated the efficacy of a multilayered conductive nanofibrous hollow conduit in harnessing both the topographical and electrical cues of the aligned conductive nanofibrous single‐walled carbon nanotube/poly (L‐lactic acid) (SWCNT/PLLA) scaffolds . Furthermore, incorporation of 1–3 wt % multiwalled carbon nanotubes (MWNTs) and 5–8 wt % poly(3‐hexylthiophene‐2,5‐diyl) (P3HT) increased the Young's Modulus by 10% and 20%, respectively, compared with using pure poly‐caprolactone .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ahn et al reported the in vivo functions of CNT‐interfaced nerve conduits in the regeneration of transected rat sciatic nerve . Kabiri et al evaluated the efficacy of a multilayered conductive nanofibrous hollow conduit in harnessing both the topographical and electrical cues of the aligned conductive nanofibrous single‐walled carbon nanotube/poly (L‐lactic acid) (SWCNT/PLLA) scaffolds . Furthermore, incorporation of 1–3 wt % multiwalled carbon nanotubes (MWNTs) and 5–8 wt % poly(3‐hexylthiophene‐2,5‐diyl) (P3HT) increased the Young's Modulus by 10% and 20%, respectively, compared with using pure poly‐caprolactone .…”
Section: Introductionmentioning
confidence: 99%
“…This method is currently popular in peripheral nerve regeneration research, and is widely considered as the gold standard evaluative tool (Gan et al, 2016; Kabiri et al, 2015; Lin et al, 2013). As expected, our results very clearly showed differences in recovery between experimental groups, and the Autograft and NCSC groups both showed improvements over time.…”
Section: Discussionmentioning
confidence: 99%
“…For each group, half was euthanized at 6 weeks, and the other at 12 weeks. We used postmortem histomorphometric analysis as a reference to justify results derived from the CatWalk system since histomorphometric analysis is widely used in current studies as a gold standard for evaluating recovery following sciatic nerve injury (Gan et al, 2016; Kabiri et al, 2015; Lin et al, 2013). We have described the methods of histomorphometric analysis in past studies (Johnson et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The use of stem cells in neural differentiation/ neuroregeneration was also reported, such as for induction of motor neuron differentiation applied with complex matrices that included collagen grafted nanofibers (Bagher et al, 2015), or peripheral nerve repair with single-walled carbon nanotubes/poly-lactic acid scaffolds (Kabiri et al, 2015).…”
Section: Biomimetic Scaffolds and Stem Cellsmentioning
confidence: 99%